Evaluasi Keakuratan Data Curah Hujan Satelit TRMM dan GPM terhadap Data Stasiun Hujan di DAS Kuranji - Rafika Andari; Nurhamidah Nurhamidah (G-Tech: Jurnal Teknologi Terapan, 2024)
Hydrological analysis require accurate rainfall data, which can be challenging. High-resolution satellite data on rainfall can be a solution. This study examines the accuracy of rainfall data in the Kuranji watershed by comparing it with satellite rainfall data from TRMM and GPM. Uncorrected and corrected data were assessed using validation techniques such as RMSE, NSE, R, and RB. The results show that rainfall can be accurately detected using GPM and TRMM satellite data. With the largest correlation value of 0.962, the GPM IMERG-F data shows superior performance. Therefore, this study recommends that GPM IMERG-F data be used for hydrological studies in the Kuranji watershed, especially in areas that do not have observational rainfall data.